The rule of law in South Korea - Mo, Jongryn, 1961-; Brady, David W. (Hoover Institution Press publication ;, 2009)
Expert contributors examine the challenges of fully implementing the rule of law in South Korea's fledgling democracy and market economy. The expert contributors detail the obstacles that must be overcome, such as corruption in politics and corporate governance and a deep-rooted cultural indifference to the rights of the individual, and offer suggestions on what can, and what should not, be done.